تحليل الحالات غير المشخصة من عسرة تصنع الورك التطورية دون سن المشي /خبرة مشفى الأسد الجامعي / - يوسف, صفوان; جوني, أحمد; زهرة, بسام (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 508 طفل دون سن المشي من مراجعي مشفى الأسد الجامعي في اللاذقية وتحري وجود عسرة تصنع الورك التطورية فتبين ما يلي: 1- نسبة حصول عدم ثبات الورك عند حديثي الولادة هو 58.55%, وتتناقص هذه النسبة إلى 5.4% في سن 4.5 شهر بعد العلاج. 2- تم دراسة 356 طفلا من سن الشهر إلى سن المشي بالفحص السريري والايكو قبل ظهور نويات التعظم والصورة الشعاعية بعد ظهورها فتبين وجود 24 طفلا مصابين بنسبة 6.74% وغالبية المرضى لم تتم دراستهم سريريا وشعاعيا بشكل جدي قبل دراستنا. 3- نؤكد على أهمية الإيكو المرافق للفحوص السريرية حتى ظهور نويات التعظم حيث تجرى الصورة الشعاعية البسيطة. We studied 508 children under the age of walking who attended Al Assad Hospital in Lattakia to investigate cases with developmental dysplasia of hip.it has been found out that: 1- The occurrence rate of hip instability in newborn babies is 58%, This rate decreases after treatment to 5.4% in age of 4.5 month. 2- We studied 356 children who aged between one month and walking age with clinical examination and ultrasound scan before the appearance of ossifying nuclei and with X-Ray after their appearance. It has been found out that 24 children suffer from this dysphasia of hip by 6.74%, and most of these patients have not been examined seriously, clinically or by scanning. 3- We emphasise the importance of using echo with clinical examination until the appearance of ossifying nuclei when we can make the simple X-Ray.